Design of basement slabs against hydrostatic uplift - Subhash Anand. (2010)
In Singapore many high-rise buildings have been supported on raft foundations. As high water table is encountered at many locations in Singapore, the base slabs of these deep foundations are subject to large hydrostatic forces. To design a base slab to withstand the loads imposed would result in massive and costly construction. Subject to soil conditions, an alternative to this problem is to use a raft foundation on a relieved or partially relieved system. This alternative appears to be attractive at locations where there are soils with very low permeability.